2010
DOI: 10.1021/bk-2010-1043.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Soy Protein-Based Polymer Blends

Abstract: A novel approach was used in the preparation of soy protein concentrate (SPC) and biodegradable thermoplastic blends. In contrast to many other soy protein (SP) blends where SP functioned merely as a filler, in this study SPC was processed as a plastic in blending with poly(lactic acid) (PLA) and poly(butylene adipate-co-terephthalate) (PBAT), respectively. The plastication of SP and blending of the resulting SP plastic with PLA or PBAT were performed in the same extrusion process. The plastication involved ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…To overcome these deficits, a sufficient amount of plasticizers and processing aids, such as glycerol, water, and sodium sulfite, have been used to lower the melting temperature of PLA and improve the processing flowability of SPC . Zhang et al found that SPC can gelate and process like a thermoplastic when adequate water and heat are present . Liu et al reported that the microstructure morphology and properties of PLA/SPC blends were significantly improved by the introduction of PEOX and polymeric methylene diphenyl diisocyanate (pMDI) as synergistic compatibilizers .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these deficits, a sufficient amount of plasticizers and processing aids, such as glycerol, water, and sodium sulfite, have been used to lower the melting temperature of PLA and improve the processing flowability of SPC . Zhang et al found that SPC can gelate and process like a thermoplastic when adequate water and heat are present . Liu et al reported that the microstructure morphology and properties of PLA/SPC blends were significantly improved by the introduction of PEOX and polymeric methylene diphenyl diisocyanate (pMDI) as synergistic compatibilizers .…”
Section: Introductionmentioning
confidence: 99%
“…To improve the mechanical properties and processability of protein-based thermoplastics, native proteins are typically denatured with heat and additives (such as urea, sodium dodecyl sulphate, and sodium sulphite) are included to facilitate protein unfolding. Protein unfolding allows the formation of intermolecular interactions in the presence of water and plasticisers, and this process generally leads to the formation of a thermoplastic protein [ 5 , 6 , 7 ]. Alternatively, protein-based thermoplastics may also be blended with other polymers to improve mechanical or physical properties, especially resistance to water when used in humid environments.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable filler have the potential of being are abundant, widely available, and more cost effective compared to their petroleum counterparts. Renewable materials, such as soy protein and other soy products, have been explored as key components in plastics and adhesive applications because of their relatively low environmental impact and strength characteristics (Reddy, Mohanty, & Misra, 2012) (Zhang & Chen, 2010).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…According to Zhang, currently soy protein in bioplastics research is classified into two types: "as a thermoplastic material for neat soy protein plastics or as a matrix polymer, and as filler for thermoplastics or thermosetting resins." Chemical modification has also been investigated and proven to improve the physical and mechanical properties soy protein plastics (Zhang & Chen, 2010) (Grewell, Carolan, & Srinivasan, 2013).…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation